Breakfast habits and its relationship to body mass index and cognitive function among final year medical students - Liyanage, G.; Siriwardana, H.D.; Wettasinghe, C.A.; Kumarasiri, M.K.H.N.; Niwanthika, T.K.I. (the author(s), publisher and licensee Medip Academy., 2017)
Background: Balanced and healthy nutrition is needed in order to avert adverse effects of poor eating practices. Children and adults often miss breakfast due to many reasons including lack of time. Evidence indicates that breakfast consumption is more beneficial than skipping breakfast following a long overnight fast. Its effect on cognitive function is still under debate. Our aim was to conduct a preliminary study to investigate breakfast habits and its effect of certain aspects of cognition in medical students in a university in Colombo, Sri Lanka. Methods: This study was a descriptive cross-sectional study. We assessed breakfast eating practices of final year medical students. Self-administered and questionnaire and trail making test for visual attention, task switching, speed of processing, and executive functioning were used as study instruments. Results: Results of 121 students were analysed. 55.4% skipped breakfast at least a day. Of them, 21 % had their breakfast ~3 days a week. Majority consumes a local meal based on rice or wheat flour. Commonest reason for missing the morning meal was lack of time (n=53, 79.1 %). There was no significant difference was found in mean BMI and trail making score between breakfast skippers and non-skippers. Conclusions: Skipping breakfast among final year medical students is common. Lack of time due to busy schedules is highlighted as a possible reason for this. Skipping breakfast did not affect some aspects of cognition and body mass index significantly. A more comprehensive case
Keywords: Students, Medical, Attention, Breakfast, Habits, Sri Lanka, Trail making test, Body mass index, Cognition